Intraoperative selective arterial calcium injection test to confirm complete resection of a proinsulinoma. Issue 7 (30th July 2022) - Sakamoto, Akimasa; Ogawa, Kohei; Iwata, Miku; Ito, Chihiro; Shine, Mikiya; Matsui, Takashi; Nishi, Yusuke; Uraoka, Mio; Utsunomiya, Takeshi; Nagaoka, Tomoyuki; Tamura, Kei; Funamizu, Naotake; et al.
Abstract: Proinsulinoma is a subtype of insulinoma that is surgically curable, but localization can be difficult as these tumors are typically too small to be visualized by imaging. We report the case of a 53-year-old woman referred to our hospital with dizziness and headache. Her blood glucose level was 46 mg/dl and Whipple's triad was present. Although her immunoreactive insulin level during hypoglycemia was in the normal range (5.0 μU/ml), the proinsulin level was elevated (408 pmol/l). Imaging examinations showed no evidence of pancreatic tumor. A preoperative selective arterial calcium injection (SACI) test showed excessive insulin secretion in the splenic artery region, which localized the proinsulinoma to the body or tail of the pancreas, and laparoscopic spleen-preserving distal pancreatectomy was performed. Intraoperative SACI test performed after tumor removal did not show excessive insulin secretion. The intraoperative SACI test appears to be useful for localization and for confirming complete resection of proinsulinoma.